Thermodynamic Study of p-Bromobenzoyl Acetone Complexes from a Temperature Variation Study: Investigating the Chelation Interaction of p-Bromobenzoyl Acetone Complexes (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The reaction of some transition metal ions like Cu(II), Co(II), Cd(II), Fe(II), Ni(II), Mn(II) and Zn(II) with p-bromo-benzoylacetone (p-BBA) have been carried out pH-metrically in 75% dioxane-water at different temperatures and the ionic strength 0.1 M (NaClO4).The order of metal ions according to the increasing stability of the complexes is found to be:Cd < Mn < Co < Zn < Ni < Fe < CuThe thermodynamic parameters G, H and S have been calculated at 30C. From these values, it is clear that the interaction between p-BBA and the metal ions is chelation.